2021
DOI: 10.3390/biology10040322
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Strain Probiotics: Synergy among Isolates Enhances Biological Activities

Abstract: The use of probiotics for health benefits is becoming popular because of the quest for safer products with protective and therapeutic effects against diseases and infectious agents. The emergence and spread of antimicrobial resistance among pathogens had prompted restrictions over the non-therapeutic use of antibiotics for prophylaxis and growth promotion, especially in animal husbandry. While single-strain probiotics are beneficial to health, multi-strain probiotics might be more helpful because of synergy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 153 publications
0
58
0
5
Order By: Relevance
“…Previous studies have suggested the beneficial effects of probiotics in the gut of wild pigs, while few studies demonstrated the mechanism behind applying probiotics strains in gut health. On the other hand, although beneficial effects of single-strain probiotics to health were revealed in numerous studies, the potential of synergistic effects from mixed probiotics strains is still not fully explored ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested the beneficial effects of probiotics in the gut of wild pigs, while few studies demonstrated the mechanism behind applying probiotics strains in gut health. On the other hand, although beneficial effects of single-strain probiotics to health were revealed in numerous studies, the potential of synergistic effects from mixed probiotics strains is still not fully explored ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The distortions mainly concern the presence or the declared number of probiotic strains in a given dietary supplement or functional product. In order to meet the distribution of counterfeit products, in 2022, an innovative tool to detect this type of irregularity was developed [ 27 ]. The probiotic identity card (PIC) relies on the collaborative action of shotgun metagenomic sequencing and the enumeration of bacterial cells using flow cytometry.…”
Section: Probioticsmentioning
confidence: 99%
“…Dunne et al and Rolfe [43,44], in 1999 and 2000 respectively, proposed that probiotics could consist of two or more microorganism combinations. The idea is to combine two or more strains of the same species, genus, or several genera of bacteria, sometimes including some fungal species like Saccharomyces [45] that could play distinct functions in the microbial processes, since the different strains could have different target at the delivery site and complement each other's effect on their host [39].…”
Section: Advent Of Combining Microorganismsmentioning
confidence: 99%
“…As a result, these compounds are connected to the antagonistic function of complex probiotics in inhibiting pathogenic bacteria or fungi present in the gastrointestinal tract. In addition, the abundance of fimbriae, which are thin protein structures located on some bacteria's cell surface, enables them to bind to the gut epithelium [45], enhancing the interaction of the isolates with each other and the host cells.…”
Section: Advent Of Combining Microorganismsmentioning
confidence: 99%